PENGOLAHAN PEPAYA MENJADI STIK SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH DAN EKONOMI MASYARAKAT DESA NUAONE - Suhartin Mohamad Syarif; Santy Permata Sari; Maria Endang Jamu (LPPM Universitas Nusa Mandiri, 2026)
Papaya is a widely available horticultural commodity in Nuaone Village, Detusoko District, Ende Regency; however, its utilization remains suboptimal and its market value is relatively low. This community service activity aims to enhance community knowledge and skills in processing unripe papaya into papaya sticks as a value-added product based on local potential. The program was implemented through socialization, training, and hands-on practice using a participatory approach, including material presentation, discussions, and assistance in production and packaging processes. The results show an increase in community understanding of local resource utilization, food processing techniques, and the importance of packaging to improve product competitiveness. Participants were able to follow all stages of production, from raw material preparation to packaging, and successfully produced papaya sticks suitable for consumption and potential commercialization as home-based products. Economically, processing papaya into papaya sticks offers higher profit opportunities compared to selling fresh papaya. The abundance of raw materials, simple production process, and relatively low capital requirements make this business accessible to the community. The product also has higher selling value, providing additional household income if produced consistently and marketed with attractive packaging. Overall, this activity positively impacts community knowledge and skills while opening opportunities for developing a local-based creative economy. Papaya stick production has strong potential as an alternative business to support community independence and improve rural welfare.